To ascertain the prevalence of clostridium difficile infection in cohort of HIV positive patients with diarrhoea at Chris Hani Baragwanath academic hospital - Shabangu, Thulisani Phillipine (My University, 2016)
Clostridium difficile infection (CDI) affects the digestive system; the symptoms range from mild to severe. In healthy individuals CDI is asymptomatic; however certain antibiotics and other medication can disturb the normal gut flora predisposing to CDI. This may lead to unnecessary hospitalisation or a prolonged hospital stay, which can be more debilitating in immunocompromised patients. Thus, judicious antibiotic use is crucial; however certain conditions require treatment that may alter normal flora, which is a predisposing factor for CDI. Objective: To ascertain the prevalence of Clostridium difficile infection in a cohort of HIV positive patients with diarrhoea at Chris Hani Baragwanath Academic Hospital. (CHBAH) over a 12 month period. Design: This was a prospective study. Methods:  Prospective study, at CHBAH  200 HIV positive patients with diarrhoea were evaluated.  Clinical records of the selected patients were accessed.  A questionnaire was used to identify risk factors for Clostridium difficile infection (CDI) in the selected patients.  Stool analysis was used to diagnose CDI. Results: Fifty-three patients (26.5%) had CDI. The most significant factors associated with an increased risk for CDI were:  Anti-tuberculous treatment; most likely Rifampicin  Antibiotic use, especially penicillin based drugs; clindamycin and carbapenems. A very low CD4 count was not a strong predictor for CDI (p=0.62) after adjusting for confounders (Viral load, concurrent co-morbid disease, use of antibiotics and anti-tuberculosis drugs). Conclusions: In our cohort of 200 patients, fifty-three (26.5%) had CDI. The risk factors identified were use of anti- TB drugs, common antibiotics associated with C.difficile.
A research report submitted to the faculty of Health Sciences, University of the Witwatersrand, in partial fulfillment of requirement for degree of Master of Medicine in Internal Medicine
Keywords: Clostridium Infections; Diarrhea; HIV